THE CHALLENGES FACED BY NEWLY GRADUATED NURSES - Ghada Magharm Alshahri, Hamad Fahad Omar Alrashidi, Bader Salem Faleh Alharbi,mohammd Mobark Saad Al Shuridah,bassam Abdullah Bassam Alnahidh, Khalood Hndy Fantool Alenezi, Ahmed Mohammed Ahmed Alabbasi, Ahmad Muraiziq Mohesn Alharbi, ,; Dhafer Mohammed M. Alzulayq, Aghadir Hamad Hassan Aldawsari, Abdulaziz Mutlaq Alzaydan, Shamsah Helyyel Alanzi, Ahmed Khudhayr Sunaytan, Masaud Saeed Alyami, Bazza Farraj Al-dosari, (Chelonian Research Foundation, 2022)
The duty for security of patients should not be confined just to the bedside nurses, but rather should be shared by all individuals throughout the healthcare system. Prior studies have found deficiencies in safety within the healthcare system, particularly among newly trained healthcare professionals. Comprehending these discrepancies and identifying effective measures to address them is crucial for guaranteeing the safety of patients. To thoroughly evaluate existing literature and provide a concise summary of the knowledge and practices related to patient safety among newly graduated registered nurses. The review used key phrases and Boolean operators to search for research publications related to the field of investigation in CINAHL, Medline, psycINFO, and Google Scholar during a period of 5 years. A total of 84 articles satisfied the criteria for inclusion, with 39 being excluded owing to including irrelevant content. Consequently, a total of 45 papers were incorporated in the literature assessment. This evaluation recognizes that nursing encompasses several phases of understanding and practicing skills. There is a discrepancy between theory and practice for new graduate nursing students, and the transition from classroom instruction is a crucial phase of learning that helps new nurses become skilled practitioners. The literature showed a lack of recognition about the newly certified nurse's understanding of patient safety. Concerns that were brought up in the 1970s are still relevant for newly graduated registered nurses today. Multiple elements influencing the transition from being a nursing student to being a newly graduated registered nurse have been identified via research. These characteristics are exposing inexperienced practitioners to possible mistakes and jeopardizing patient safety. Keywords: newly graduated nurses, literature review, nursing students, difficulties.